Conceptualizing Change: A proposed Shift in Global Discourse Surrounding Disability in Language Teaching - Rosa Dene David; Caroline Torres (Universidad de La Sabana, 2020)
Conceptualización del cambio: una propuesta de cambio en el discurso global en torno a la discapacidad en la enseñanza de idiomas Conceptualização da mudança: uma proposta de mudança no discurso global em torno da deficiência no ensino de línguas This editorial proposes a conceptual and instructional shift surrounding educating English learners with disabilities.  Individuals with disabilities are the largest minority group in the world, yet in many classrooms across the world, they often lack the opportunities and support needed to be successful.  This is especially apparent in English as a second or foreign language classrooms, where students with disabilities need first to be included and then provided with structured and systematic supports to be successful.  We suggest that an initial shift in the way that we think about disability is a necessary first step.  This can then be supported by using Universal Design for Learning as a framework to reduce barriers in instruction and increase access and success for English learners.  This editorial also introduces five articles, which aim to further the discourse and understanding of how to support individuals with disabilities learning English across countries and contexts. To reference this article (APA) / Para citar este artículo (APA) / Para citar este artigo (APA) David, R. D. & Torres, C. (2020). Conceptualizing change: A proposed shift in global discourse surrounding disability in language teaching. Latin American Journal of Content & Language Integrated Learning, 13(1), 9-25. https://doi.org/10.5294/laclil.2020.13.1.1 Published: 28/08/2020